Enhancing Driver Factors of Rice Productivity and Farm Profitability - Cahyati, Nia; Noer, Irmayani; Kurniawan, Henry (AIBPM Publisher, 2024)
The research aimed to analyze the external factors influencing the production and income of lowland rice farmers in South Lampung Regency, Lampung Province. Using both qualitative and quantitative methods, the study followed four stages: data collection, input, analysis, and interpretation. The research involved 50 farmers from the Sidomulyo District, with data gathered through questionnaires and interviews. The study identified key external factors affecting production, including land area (X1), seeds (X2), fertilizer (X3), pesticides (X4), and labor (X5). The production function was modeled as Ln Y = Ln 9.111 + 1.010 Ln X1 + 0.072 Ln X2 – 0.137 Ln X3 + 0.023 Ln X4 + 0.012 Ln X5, showing an increasing return to scale with a significance value 0.05. This suggests that greater use of these production factors enhances rice production. The analysis revealed a good income of IDR 10,592,864.74, with R/C and B/C cash ratios exceeding 1, confirming that lowland rice farming in South Lampung Regency remains profitable. The study concludes that external factors significantly impact rice production and income, with potential for increased profitability through optimized resource use